Quantitative insights into green purchase intentions: The interplay of health consciousness, altruism, and sustainability - Phi-Hung Nguyen; Dat Ngoc Nguyen; Lan Anh Thi Nguyen (Cogent Business & Management, 2023)
Green consumption behaviour research plays a vital role in promoting actions to protect the environment and promote sustainable development. This research aims to determine the relationship between environmental sustainability awareness, social sustainability awareness, altruism, health consciousness, and consumers' green consumption behaviour. A quantitative analysis based on a dataset of 586 customers was performed to test the hypotheses with SmartPLS 3.3.3. The results of the PLS-SEM model indicated as follows: (1) Awareness of the sustainable environment enhances customers' altruism; (2) Altruism has a positive effect on customers' intention, loyalty, and green brand evangelism; (3) Health consciousness has a positive effect on attitude but has no effect on green purchase intention; (4) Green purchase intention has a positive effect on loyalty and green brand evangelism; (5) However, green brand loyalty is not a factor that influences green brand evangelism, which is a significant finding. Furthermore, another research finding also highlights the importance of altruism in utilizing green products.
Keywords: 650; environment sustainability awareness; green brand evangelism; green brand loyalty; green purchase intention; health consciousness; social sustainability awareness